Музей как место социальных связей. Фабрика Шиндлера в Кракове и Музей истории польских евреев По́лин в Варшаве - BOGUNIA-BOROWSKA, Małgorzata (Мониторинг общественного мнения: экономические и социальные перемены, 2016)
Museums are ambiguous spaces. On the one hand, they provide some models built on social perceptions, and on the other, they are places open to interpretation. They are relational spaces. Spaces of various types of relations like institutional, interpersonal, international, intergeneration or intercultural relations. They are also places of relations and dialogue, establishing and negotiating meanings. In any event, museums are also, and perhaps above all, stories about people, events and the effects of their meetings. The article presents the results of qualitative research devoted to the reception of the museum, which was conducted in two museums the Museum of Oskar Schindler’s Enamel Factory in Krakow and the Museum of the History of Polish Jews POLIN in Warsaw. The project was titled «My way, my choice». Special attention is paid to the imaginative and relational character of the museum space.